Plantation forests driven spatiotemporal vegetation trends and its interplay with climate variables in the Northwestern Highlands of Ethiopia - Bireda Alemayehu; Juan Suarez-Minguez; Jacqueline Rosette (International Journal of Applied Earth Observations and Geoinformation)
Plantation forests have been increasingly established in Fagita Lekoma District, located in the Northwestern Highlands of Ethiopia, over the past two decades. However, their interaction with climate variables remains largely unexplored. This study aims to investigate the spatiotemporal dynamics of plantation forests driven vegetation changes and their relationship with climate variables in the district from 2000 to 2020. Moderate Resolution Imaging Spectroradiometer (MODIS) data and Enhanced National Climate Services (ENACTS) data of the study area were processed for 21 years to examine trends using the Mann-Kendall test and Sen’s slope estimator, employing R 4.3 programming software. Concurrently, various climatic data, including evapotranspiration (ET), land surface temperature (LST), and rainfall, were processed, and analysed to explore the relationships between vegetation change and climate variability in the district during the study period. Increasing trends of Normalized Difference Vegetation Index (NDVI) greenness in the district were highlighted, with mean annual NDVI rising from 0.53 to 0.64, showing an average trend of 0.0036 year−1. This increase is primarily attributed to the widespread establishment of plantation forests across the district. The largest increase was revealed in ET, with a rate of 12.27 kg/m2 year−1. Conversely, LST and rainfall exhibited insignificant decreasing trends, with a rate of − 0.15 °C year−1 and − 10.54 mm year−1, respectively. Furthermore, a statistically significant positive correlation between NDVI and ET was observed, underscoring the critical role of vegetation in maintaining water availability. The negative correlation between NDVI and LST suggests that increased vegetation cover contributes to land surface temperature cooling. Additionally, the statistically insignificant negative correlation between NDVI and rainfall emphasizes the influence of land use change and human intervention on vegetation productivity. Overall, this study highlights the significance of long-term satellite observations in assessing the intricate interplays between vegetation dynamics driven by plantation forestry and climate variables at a local scale. The findings emphasize the role of plantation forests in enhancing vegetation greenness, improving water regulation, and mitigating land surface temperature warming, providing critical insights for sustainable land management and policy interventions in similar regions.